An integrative description of a new tardigrade species Mesobiotus romani sp. nov. (Macrobiotidae: harmsworthi group) from the Ecuadorian Pacific coast - Roszkowska, Milena; Stec, Daniel; Gawlak, Magdalena; Kaczmarek, Łukasz (Zootaxa, 2018)
In a mixed moss and lichen sample collected in Esmeraldas Province in north-western Ecuador, 20 tardigrades and 11 eggs, belonging to a new species of the genus Mesobiotus, were found. In addition to the traditional taxonomic description with morphometrics, light and scanning microscopy imaging, we also provide nucleotide sequences of three nuclear (18S rRNA, 28S rRNA, ITS-2) and one mitochondrial (COI) DNA fragments of the new species. Based on the egg chorion morphology, Mesobiotus romani sp. nov. is the most similar to: M. binieki, M. coronatus, M. dimentmani, M. patiens, M. perfidus, M. philippinicusi, M. pseudoblocki, M. pseudocoronatus, M. pseudopatiens, M. radiatus, M. rigidus, M. simulans and M. wuzhishanensis, but differs mainly by some specific characters of both egg and adult morphology, and morphometrics.